Plan de negocio para la creación de una cafetería en la ciudad de Jipijapa - Angulo Paredes, Alex Bryan (2020)
The present investigation consists of an undertaking for which a business plan was designed, with the following specific objectives: Carry out a market study on a coffee shop in the city of Jipijapa that defines the target market and the preferences of the inhabitants, elaborate market strategies to attract customers in a cafeteria, design the organizational structure of the business, conduct a financial study to determine the profitability of a business plan. It was justified from the theoretical point of view with the conceptualizations about coffee, entrepreneurship, marketing, business and finance. In the methodological part, a qualitative and quantitative approach was used, with interviews and personal surveys, applied by means of questionnaires, designed based on the research variables…………..